(untitled) (Ameghiniana, 2015)
The analysis of two-stiped dichograptids, largely of baltograptid and expansograptid taxa of the family Didymograptidae from the Floian of northwestern Argentina, provides insight into the evolutionary relationships of this group. The important proximal end characters clearly cluster the baltograptids with the derived genera Didymograptus and Aulograptus. One of the analyses provides the information that the genera Cymatograptus and Expansograptus share a common ancestor but are not closely related to the two-stiped Kiaerograptus and related taxa. Likewise, with the exception of some controversial taxa, the families Tetragraptidae and Didymograptidae can be readily differentiated, supporting previous interpretations that they represent monophyletic clades. Although the present analyses are poorly supported, they provide hypotheses that could be further tested based on new data on isolated dichograptid taxa based on isolated or relief-preserved material. Resumen. EXPLORANDO LAS RELACIONES FILOGENÉTICAS DE LOS REGISTROS DE GRAPTOLITOS DEL FLOIANO (ORDOVÍCICO) DE ARGENTINA MEDIANTE ANÁLISIS CLADÍSITICO. El análisis de los dichográptidos de dos estipes, principalmente taxones de baltográptidos y expansográptidos de la familia Didymograptidae, del Floiano del noroeste de Argentina, permite establecer relaciones evolutivas para este grupo. Los caracteres del extremo proximal resultan importantes para agrupar claramente a los baltográptidos con los géneros derivados Didymograptus y Aulograptus. Uno de los análisis indica también que los géneros Cymatograptus y Expansograptus comparten un ancestro común, aunque no se hallan cercanamente relacionados con otros taxones de dos estipes, como el género Kiaerograptus y los taxones relacionados. A excepción de algunos taxones controversiales, las familias Tetragraptidae y Didymograptidae se diferencian notablemente a través de este análisis, justificando las interpretaciones previas de que ambas constituirían clados monofiléticos. Aunque los análisis presentados se encuentran pobremente soportados, proveen hipótesis que podrían ser comprobadas a la luz de mayor información proveniente de taxones de dichográptidos aislados o conservados en relieve